The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/mnras/staa2215
|View full text |Cite
|
Sign up to set email alerts
|

A chemical study of carbon fractionation in external galaxies

Abstract: In the interstellar medium carbon exists in the form of two stable isotopes 12C and 13C and their ratio is a good indicator of nucleosynthesis in galaxies. However, chemical fractionation can potentially significantly alter this ratio and in fact observations of carbon fractionation within the same galaxy has been found to vary from species to species. In this paper we theoretically investigate the carbon fractionation for selected abundant carbon-bearing species in order to determine the conditions that may l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The 12 C/ 13 C ratios obtained in NGC 253 in the literature are 21 ± 6 (Martín et al 2019b) from C 18 O/ 13 C 18 O, which is close to our obtained values. However, note that the 12 C/ 13 C ratio can also depend on the species because of fractionation (Colzi et al 2020;Viti et al 2020).…”
Section: Column Densities and Ratiosmentioning
confidence: 99%
“…The 12 C/ 13 C ratios obtained in NGC 253 in the literature are 21 ± 6 (Martín et al 2019b) from C 18 O/ 13 C 18 O, which is close to our obtained values. However, note that the 12 C/ 13 C ratio can also depend on the species because of fractionation (Colzi et al 2020;Viti et al 2020).…”
Section: Column Densities and Ratiosmentioning
confidence: 99%
“…In particular, Viti et al (2011), and later Benedettini et al (2013), found that at least some of the species observed in B1 were likely the product of a non-dissociative, C-type shock with pre-shock density n(H) ≥ 10 5 cm −3 and shock velocity V s ∼ 40 km s −1 . In this section, we use their same (updated) chemical and shock time dependent gas-grain model, UCLCHEM (Holdship et al 2017), augmented with the nitrogen and carbon isotopologues chemistry (Viti et al 2019(Viti et al , 2020, to determine whether, theoretically, we should expect the passage of a shock to affect the nitrogen fractionation in L1157-B1. Full details of the chemical and shock model UCLCHEM can be found in the references above.…”
Section: Models Of Nitrogen Fractionation In Shocksmentioning
confidence: 99%
“…We further note that the center of NGC 7465 does not exhibit particularly unusual levels of photodissociation in general, as its [C II]/CO line ratio is typical for nearby spiral galaxies (Figure 14). Finally, Viti et al (2020) argue that fractionation is unlikely to be a significant effect for the CO isotopologues in typical conditions, though it may be more important for other molecular species.…”
Section: Csmentioning
confidence: 94%